An investigation into facilitating learning via the whole brain model in the Study Unit of Toothmorphology - De Boer, Ann-Louise (University of Pretoria, 2013)
Dissertation (MEd (Curriculum, Instructional Design and Development))--University of Pretoria, 2007.